Slovenia : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper reviews economic developments in the Republic of Slovenia during 1990-97. Output began to recover in 1993, and by 1996, Slovenia's GDP was back to its pre-independence level. Domestic demand was the main driving force, while the growth of exports fluctuated in line with the business cycle in Western Europe and changes in competitiveness. A strong external contribution brought the GDP growth rate to a peak of 5.3 percent in 1994 but it subsequently slowed, reaching 3.1 percent in 1996. GDP growth picked up again in 1997.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet